Effects of harvesting corn varieties at varying maturities on silage quality and digestible dry matter yield of corn silages - Suphi Deniz; Hüseyin Nursoy; İbrahim Yılmaz; M. Akif Karslı (Eurasian Journal of Veterinary Sciences)
The objective ol this study was to evaluate the effects of harvesting corn varieties (Hx-947, 33-94. Frassino and Arifiye) at varying maturities on chemical composition, silage quality and digestible dry matter (DM) yields ol corn silages. Corn varieties were harvested at early-milk, milk, and dough stages and were ensiled in mini-silos (1L in volume) in triplicate tor each variety and maturity. Packing was accomplished by hand-power. After 60 d of incubation, silages were opened and analyzed for DM. organic matter (OM), crude protein (CP), neutral detergent fiber (NDF). acid detergent liber (ADF), pH, lactic acid, acetic acid, propionic acid, butyric acid concentrations, and in vitro DM digestibility (IVDMD). In general, the concentrations of DM and OM increased, but NDF, ADF concentration decreased with increasing maturity in silages (P<0.05). The changes in concentration of CP were variable among corn varieties. Even though silage pH increased with increasing maturity, all silage pH were around recommended optimal pH value ol 3.5-4.5. Silage organic acid contents were generally in a desirable range (low in acetic and butyric acid and high in lactic acid content) and correlated with pH values. While IVDMD of 33-94 (77.16% and 76.80) and Frassino (79.18 and 78.48) were the highesl (P<0.05) at early-milk and milk stages, respectively, IVDMD of silages were similar at dough stage (P>0.05). 33-94 variely had the highest digestible DM yields ai early milk and milk stages (1142.4 and 1363,7 kg/da, respectively), but Arifiye variety had the highest digestible DM yield (1232.9 kg/da) at dough stage. In conclusion, while milk stage seemed to be the best harvesting stage for Rx-947, 33-94 and Frassino varieties, dough stage seemed to be the best harvesting stage for Arifiye variety based on digestible DM yields.